The Impact of the Arabic Language on Socialization - Tahseen, Assistant Prof. Dr. Asil Raad Tahseen (Sulaimani Journal for Humanities, 2026)
This research aims to explore the role of the Arabic language in socialization, as it is the primary means of communication and the transmission of values and customs among individuals. Through language, individuals learn cultural and social norms adopted by society, such as etiquette, ethics, and religious beliefs. The Arabic language also contributes to shaping individual identity and strengthening cultural belonging, which helps maintain social cohesion and understanding among community members. Additionally, the Arabic language enhances interaction between different generations, supporting social traditions and ensuring their continuity
Keywords: Language; Socialization; Arabic; Social